Death, decomposition, and detector dogs - Stejskal, Susan M., author.
1 online resource
Keywords: "Death, Decomposition, and Detector Dogs: From Science to Scene, Second Edition is designed to help canine handlers, detectives, death investigators, crime scene personnel (including forensic laboratory personnel, technicians, and supervisors), and attorneys understand the science involved when utilizing human remains detector (HRD) canines as a locating tool. The book covers the basic anatomy and physiology of canine olfaction and the unique characteristics of their scenting ability that allows dogs to be trained to locate distinct odors. Using concise and clear explanations and photographs, the book reviews the science of forensic taphonomy. Factors that may affect the decomposition process are highlighted along with what the potential outcomes that may be encountered. The book examines how the odor of human remains is generated through various stages of decomposition and the manner in which environmental conditions in both land and water settings may affect that odor. Different types of background information that may help in determining possible search locations for missing individuals are included as well as assist the HRD canine handler in developing search plans are covered. Different tools and technologies that may be used in addition to an HRD canine team are included to help readers understand that are many ways to address searching for a decedent. Several case reports involving decedents, found in both land and water settings in addition to different weather conditions, are included to help the reader understand how the environment may have affected the condition of the decedent. This edition includes more case reports explaining how environmental factors were considered in HRD canine deployments in both land and water settings. Understanding which variables-and how such variables-can affect the state and condition of human remains, as well as dispersion of odor from human remains, will help canine handlers utilize their HRD canine more effectively as a locating tool. Death, Decomposition, and Detector Dogs, Second Edition will help HRD canine handlers and other law enforcement personnel be better prepared to meet the challenges of their jobs before, during, and after searches for the missing"--